Cybersecurity Framework for Requirements of Repair, Update, and Renovation in Industry 4.0 - Ilhan, Ismail; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2019)
In order to capture technological progress and industrial development, organizations need some transformation and change. Therefore, device exchange to existing systems, adding new technological devices, update to software systems are performed. In addition, product replacement and software downloads can be performed during the elimination of faults in the existing system. This repair, update, and renewal of industrial systems require possible cybersecurity requirements. In order to implement cybersecurity in a healthy way, it needs to be accepted from some stages and systems. These stages and systems may vary depending on the models and technologies of the systems in industry 4.0. In this study, cyber systems used in industry are discussed and the cybersecurity framework is proposed for repairing, updating and renewing systems in general. They claim that the given framework will be a reference to cybersecurity requirements in industry 4.0. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: cybersecurity; Industry 4.0; renovation; repair; requirements of security; update